Sistem Informasi Administrasi Pembayaran SPP Pada SD PGRI Kota Denpasar - wirayanti, Ni Putu Eka; Sugiartawan, Putu; Suryawan, I Wayan Dharma (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
Abstract. The development of information technology is currently running rapidly to reach all fields, one of which is in the field of education. In educational institutions, it requires good management of data management to meet student needs. The administrative payment system in the field of education is very important to record student administration payment payments at the school. Accuracy and accuracy in the payment system are the main factors in obtaining effective and efficient results. With the use of these computers, will make it easier to process data and is very influential in work effectiveness. So the existence of information technology is a means to facilitate the community in managing data and presenting information in an educational institution. To solve this problem, it is necessary to have the right solution in the form of an administrative information system at SD PGRI Denpasar City. The use of this information system will have a positive impact in carrying out administration and make it easier for 2 staff employees to enter the names of students, then be able to record anyone who has not or is late in paying the tuition fee. Based on the description, the title of the research to be made is the Design of Administrative Information Systems at SD PGRI Denpasar City Based on a Website.